Group A β-hemolytic streptococcus causing purpura fulminans: two case reports - Alkhatatbeh, A.; Chen, Jiechen; Chen, Yongru; Ma, Zebin; Chen, Hongjiang; Chen, Bin; Zhou, Yongfei; Xia, Xue; Huang, Xiaoqing; Hong, Shuting; Hu, Jun (Frontiers in Immunology, 2026)
Purpura fulminans (PF) is a rare, life-threatening emergency characterized by rapidly progressive purpura evolving into hemorrhagic bullae and skin necrosis due to dermal microvascular thrombosis, typically accompanied by shock and disseminated intravascular coagulation (DIC). We report two fatal adult cases of infection-associated PF caused by Streptococcus pyogenes (group A streptococcus). Both patients presented with early gastrointestinal symptoms and rapidly developed septic shock, severe coagulopathy compatible with overt DIC, and extensive lower-limb purpura with bullae and necrosis. Pathogen identification was supported by next-generation sequencing from blood and/or tissue specimens. Management required immediate resuscitation, organ support, targeted anti–group A streptococcal therapy, and surgical source control; nevertheless, both patients deteriorated with refractory multiorgan failure. These cases highlight that gastrointestinal symptoms may precede fulminant invasive S. pyogenes infection with PF and streptococcal toxic shock syndrome overlap. Early recognition of the clinical pattern (shock + rapidly progressive purpura/bullae + DIC) and aggressive multidisciplinary management are essential.